2005
DOI: 10.1074/jbc.m407019200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nitration and Chlorination Sites on Apolipoprotein A-I Catalyzed by Myeloperoxidase in Human Atheroma and Associated Oxidative Impairment in ABCA1-dependent Cholesterol Efflux from Macrophages

Abstract: We recently reported that apolipoprotein A-I (apoA-I), the major protein component of high density lipoprotein, is a selective target for myeloperoxidase (MPO)-catalyzed nitration and chlorination in both and serum of subjects with cardiovascular disease. We further showed that the extent of both apoA-I nitration and chlorination correlated with functional impairment in reverse cholesterol transport activity of the isolated lipoprotein. Herein we used tandem mass spectrometry to map the sites of MPO-mediated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
207
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(224 citation statements)
references
References 55 publications
15
207
0
2
Order By: Relevance
“…We demonstrated previously that apoA-I recovered from human atherosclerotic lesions is heavily oxidized (7)(8)(9)18), a finding that others have replicated (6,19,20). Proteomic identification of oxidatively modified sites within apoA-I isolated from atherosclerotic lesion by immunoprecipitation with apoA-I-specific antibodies identified a number of preferred residues for MPO-and NO-derived oxidant PTMs (8,9).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…We demonstrated previously that apoA-I recovered from human atherosclerotic lesions is heavily oxidized (7)(8)(9)18), a finding that others have replicated (6,19,20). Proteomic identification of oxidatively modified sites within apoA-I isolated from atherosclerotic lesion by immunoprecipitation with apoA-I-specific antibodies identified a number of preferred residues for MPO-and NO-derived oxidant PTMs (8,9).…”
mentioning
confidence: 57%
“…Nitrated at Position 166-We first reported that apoA-I was a preferential target of protein nitration within atherosclerotic lesions, and in our later studies, NO 2 -Tyr 166 -apoA-I was identified as a preferred site of nitration using proteomics studies (7,8). We initially sought to develop an mAb that specifically recognized this site-specific nitrated apoA-I to better study its abundance and particle distribution.…”
Section: Monoclonal Antibody 4g112 Recognizes Apoa-i Selectivelymentioning
confidence: 99%
See 2 more Smart Citations
“…It catalyzes the two-electron peroxidation of chloride to generate hypochlorous acid (HOCl) [2], a potent chlorinating oxidant, capable of chlorinating tyrosine into chlorotyrosine. Levels of chlorotyrosine are increased in atherosclerotic tissues [3] and the blood of in patients with inflammatory conditions including atherosclerosis [4,25,26]. The chlorination of apolipoprotein A-I was found to impair its cardioprotective ability to remove excess cellular cholesterol from lipid-laden macrophages in the artery wall [5].…”
Section: Introductionmentioning
confidence: 99%